A model for dual health care market with congestion differentiation. Issue 2 (17th October 2022) - Besancenot, Damien; Lamiraud, Karine; Vranceanu, Radu
Abstract: The French market for specialist physician care has a dual legal structure: physicians must exclusively work in sector 1 and charge regulated fees or in sector 2, where they can freely set their fees. Patient out‐of‐pocket payments in sector 2 are partially covered by private insurance. The primary differentiating factor between both sectors is the number of patients per specialist, which in turn directly affects the overall quality of the service provided. We built an equilibrium model to analyze both specialists' decisions about which sector to work in, and patients' choice of physician and therefore sector. More specifically, the model allowed us to study the effect of changes in prices and economy‐wide patient‐to‐specialist ratios on profits and patients' utility associated with the services provided in each sector.